Andersen–Tawil Syndrome Is Associated With Impaired PIP(2) Regulation of the Potassium Channel Kir2.1 - Handklo-Jamal, Reem (Front Pharmacol, 2020)
Andersen–Tawil syndrome (ATS) type-1 is associated with loss-of-function mutations in KCNJ2 gene. KCNJ2 encodes the tetrameric inward-rectifier potassium channel Kir2.1, important to the resting phase of the cardiac action potential. Kir-channels’ activity requires interaction with the agonist phosphatidylinositol-4,5-bisphosphate (PIP(2)). Two mutations were identified in ATS patients, V77E in the cytosolic N-terminal “slide helix” and M307V in the C-terminal cytoplasmic gate structure “G-loop.” Current recordings in Kir2.1-expressing HEK cells showed that each of the two mutations caused Kir2.1 loss-of-function. Biotinylation and immunostaining showed that protein expression and trafficking of Kir2.1 to the plasma membrane were not affected by the mutations. To test the functional effect of the mutants in a heterozygote set, Kir2.1 dimers were prepared. Each dimer was composed of two Kir2.1 subunits joined with a flexible linker (i.e. WT-WT, WT dimer; WT-V77E and WT-M307V, mutant dimer). A tetrameric assembly of Kir2.1 is expected to include two dimers. The protein expression and the current density of WT dimer were equally reduced to ~25% of the WT monomer. Measurements from HEK cells and Xenopus oocytes showed that the expression of either WT-V77E or WT-M307V yielded currents of only about 20% compared to the WT dimer, supporting a dominant-negative effect of the mutants. Kir2.1 sensitivity to PIP(2) was examined by activating the PIP(2) specific voltage-sensitive phosphatase (VSP) that induced PIP(2) depletion during current recordings, in HEK cells and Xenopus oocytes. PIP(2) depletion induced a stronger and faster decay in Kir2.1 mutant dimers current compared to the WT dimer. BGP-15, a drug that has been demonstrated to have an anti-arrhythmic effect in mice, stabilized the Kir2.1 current amplitude following VSP-induced PIP(2) depletion in cells expressing WT or mutant dimers. This study underlines the implication of mutations in cytoplasmic regions of Kir2.1. A newly developed calibrated VSP activation protocol enabled a quantitative assessment of changes in PIP(2) regulation caused by the mutations. The results suggest an impaired function and a dominant-negative effect of the Kir2.1 variants that involve an impaired regulation by PIP(2). This study also demonstrates that BGP-15 may be beneficial in restoring impaired Kir2.1 function and possibly in treating ATS symptoms.